FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEKAMBUHAN PASIEN SKIZOFRENIA DI RUANG RAWAT INAP RUMAH SAKIT JIWA DAERAH PROVINSISUMATERA UTARA MEDAN TAHUN 2022 - MURNI ARITONANG (LP2MTBM MAKARIOZ, 2022)
Schizophrenia is the most severe mental illness experienced by humans, it can even be considered worse than sufferers of the Human Immunodeficiency Virus (HIV), not because it cannot be treated, but because it takes a long time to heal, and relapses occur at times. The population in this study were families of patients who had family members with schizophrenia who were treated more than once. The data obtained in this study were statistical tests using the chi-square test showing that there was a relationship between the incidence of recurrence and the regularity of taking medication with a probability value (pv = 0.047 < pv = 0.05). And the incidence of recurrence with family support has a probability value (pv = 0.025 < pv = 0.05).